Faktor Risiko Yang Mempengaruhi Kinerja Proyek Pada Perusahaan Konstruksi (Studi Kasus : Pada CV. Gresik Mitra Teknik) - Bahari, Chabib; Suci, Ragil Dewi (Fakultas Ekonomi Universitas Gresik, 2019)
The relationship of risk factors to the performance project becomes veryimportant in improving the efficiency and the steps that can be done to address these risk factors. The process of risk management project is the identification of risk factor, risk analysis, risk evaluation and risk management measures. The objective of this study is to find out the risk factors affecting the performance project of a self managed building construction management in a CV. Gresik Mitra Teknik. Research to determine the risk factor conducted qualitatively, by analyzing the perception data obtained from interviews, observations, and documentation. The result of the data analysis shows there are two major risk factors that affect the performance project in CV. Gresik Mitra Tekhnik, that is : changes in project execution schedule and labor recruitment is not timely.ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â Keywords : Risk Management, Risk Factors, Performance Project, and Construction.DOI : 10.5281/zenodo.3474551